Unveiling the role of erinacines in the neuroprotective effects of Hericium erinaceus: a systematic review in preclinical models - E. T. Spangenberg; A. Moneypenny; G. G. Bozzo; M. L. Perreault (Frontiers in Pharmacology)
The medicinal mushroom lion’s mane (Hericium erinaceus) is suggested to have therapeutic potential for neurological disorders due to its neuroprotective and neurotrophic properties. Mycelia of H. erinaceus contain erinacines, a group of cyathane diterpenoids, however no systematic review has explored the broader role of these compounds in mediating the neurobiological effects of the mushroom. This systematic review was therefore performed to enhance the depth of understanding surrounding the neurobiological impact of the various erinacine compounds using various cellular and rodent models. A secondary focus was to assess how study outcomes were influenced by the chemical complexity of the administered treatments. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were utilized. The findings showed the broader potential of H. erinaceus mycelial formulations, and their derived erinacines, to exert dose-dependent benefits in motor, cognitive, and depression-like behaviours in animal models. Synthesis of records highlighted the ability of both erinacines and H. erinaceus to induce antioxidant responses and activate pro-survival signaling pathways. However, erinacine A and C uniquely induced the accumulation of the transcription factor Nrf2, a key regulator of the antioxidant response. These erinacines were also anti-inflammatory, enhanced neurogenesis and cell survival, and improved cognitive and behavioral outcomes in vivo. These findings suggest the promise of H. erinaceus extracts and individual erinacines as accessible, cost-effective interventions for aging-related and neurodegenerative conditions.